Operation of kinetic-inductance travelling wave parametric amplifiers at millimetre wavelengths - Tan, B; Klimovich, N; Stephenson, R; Faramarzi, F; Day, P (IOP Publishing, 2024)
It is expected that the operation of microwave Kinetic Inductance Travelling Wave Parametric Amplifiers (KITWPAs) can be extended to the millimetre (mm) and the sub-mm wavelength range as long as the frequency is below the gap frequency of the superconducting film. This paper presents possible mm-wave designs for KITWPAs based on microstrip transmission lines. Our device is designed based on the BCS (Bardeen-Cooper-Schrieffer) model which successfully reproduces the measured transmission profile, gain, bandwidth, and nonlinear response of a fabricated KITWPA operating in the Ka-band, and includes the millimetre-wave dielectric loss determined by fitting the quality factor of a Wband microstrip resonator. We suggest a layout for a KITWPA operating near 220 GHz that can be fabricated using the same superconducting properties as the Ka-band device and can be coupled to a waveguide system. We conclude the paper by extending the 220 GHz design to higher frequency regimes approaching 1 THz.